PERBEDAAN INTERPRETASI HUKUM MENIKAHI WANITA HAMIL (Analisis Terhadap Pasal 53 Kompilasi Hukum Islam Perspektif Maqhosid Syari’ah) - Sholeh, M. Gunawan Ismail (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Law is a controller of human behavior, but not the least of the legal rules there are different interpretations. KHI as the law that regulates marriage in Indonesia cannot be separated from this, namely Article 53 concerning Pregnant Marriage. In regulating human life, law must consider the aspects of benefit and harm (maqhosid syrai'ah). The purpose of this paper is to clarify the purpose of KHI Article 53 as law. In this study the method used is a qualitative research method and uses the Maqhosid Syari'ah approach. While the sources of data collection in this study are books, articles, manuscripts or the like related to similar themes. The data analysis methods in this study are collecting data, reducing data, presenting data and drawing conclusions. Based on the analysis conducted by KHI Article 53 which regulates pregnant marriage accommodates the maqhosid syari'ah aspect, namely the benefit of protecting honor and offspring.